2008
DOI: 10.1016/j.eurpsy.2008.01.463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of once-daily extended release Quetiapine Fumarate (Quetiapine XR) as add-on to antidepressants in major depressive disorder (MDD)

Abstract: Objective:To evaluate the efficacy and tolerability of once-daily quetiapine XR adjunctive to antidepressant therapy versus antidepressant alone in patients with MDD showing an inadequate response to antidepressant treatment (mainly SSRIs/SNRIs).Methods:6-week, multicentre, double-blind, parallel-group study (D1448C00007). Patients were randomised to receive quetiapine XR 150mg/day (n=167), 300mg/day (n=163) or placebo (n=163) as add-on to maintained antidepressant treatment. Primary endpoint: baseline to Week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One study 28 found the 300 mg dose to be more effective than placebo, but not the 150 mg dose. The second study 27 showed that both doses were more effective than placebo. Although quetiapine appears to be an effective adjunctive agent for MDD, minimally effective and optimal doses of quetiapine for this indication remain unclear.…”
Section: Efficacy Trialsmentioning
confidence: 98%
See 1 more Smart Citation
“…One study 28 found the 300 mg dose to be more effective than placebo, but not the 150 mg dose. The second study 27 showed that both doses were more effective than placebo. Although quetiapine appears to be an effective adjunctive agent for MDD, minimally effective and optimal doses of quetiapine for this indication remain unclear.…”
Section: Efficacy Trialsmentioning
confidence: 98%
“…Two other studies 27,28 focused on the use of quetiapine augmentation of antidepressants. These studies examined two separate doses of quetiapine (150 mg or 300 mg).…”
Section: Efficacy Trialsmentioning
confidence: 99%